Glossary of political science terms: Islamic and western - Moten, Abdul Rashid; Abdel Salam, El Fatih Abdullahi (Thomson Learning, 2005)
This book provides a clear and lively introduction to selected Islamic and Western political science terms. It is the first of its kind, combining Political Science terms from the two streams and presents succinct definitions and explanations of around 2,000 key concepts in an engaging style.